Reconsidering systemic fear and the stock market: A reply to Baines and Hager - James McMahon (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2020)
A recent New Political Economy article by Baines and Hager (2020) critiqued Shimshon Bichler and Jonathan Nitzan's capital-as-power (CasP) model of the stock market (Bichler & Nitzan, 2016). Bichler and Nitzan's model of the stock market seeks to explain how financial crises are tied to the (upper) limits of redistributing income through power. Bichler and Nitzan use American financial data to show that "U.S.-based capitalists" have risen to a great height of power, relative to the underlying population. This height also produces a "forward-looking" fear about the ability to accumulate even more (Bichler & Nitzan, 2016). Baines and Hager took the important step of examining the CasP model with financial data from four other countries-France, Germany, Great Britain and Japan. They argue that these countries follow some of the patterns of the United States, but not all. These differences in patterns matter because Baines and Hager are curious to know how the CasP model of the stock market can function as a general model of capital accumulation at an international level. This paper will respond to the part of Baines and Hager's paper where they analyze "systemic fear" in the stock markets of France, Germany, Great Britain and Japan. It argues that Baines and Hager were perhaps too quick to dismiss systemic fear as a concept to study national and regional differences in international political economy. This concept is still in its infancy and, with more consideration, there are opportunities to investigate the characteristics of systemic fear. By re-examining systemic fear in twelve countries, this paper will show the potential for the concept of systemic fear to support the study of capitalist crisis and national diversity in capitalist development.
Keywords: 330; capital as power; stock market; systemic crisis; systemic fear